Relationship between plasma high-sensitivity C-reactive protein and traditional cardiovascular risk factors among active-duty military personnel in the Republic of Serbia - Ratković , Nenad; Pandrc, Milena; Perić, Vitomir; Stojanović, Maja; Rančić, Nemanja (Vojnosanitetski pregled, 2022)
Background/Aim. Approximately one-third of individuals with only one cardiovascular (CV) risk factor or without any, as well as 40% of individuals with a concentration of cholesterol less than average, die from CV diseases (CVD). Recent studies underlined the significant role of inflammation in atherosclerosis and its complications. The aim of this study was to analyze the association of high-sensitivity C-reactive protein (hs-CRP) with traditional risk factors for coronary heart disease. This is the first such study in Serbia. Methods. This is an observational cross-sectional study, which included active-duty military personnel of similar socio-epidemiological and economic characteristics. Plasma hs-CRP and traditional CV risk factors were evaluated. The relative CV risk was staged as low (hs-CRP  3 mg/L). The Systematic Coronary Risk Evaluation (SCORE) system was used for absolute CV risk assessment and total risk (fatal and non-fatal events). Results. The study included 205 participants, average age of 39 (35–43) years, with median and interquartile range values of hs-CRP 0.80 mg/L (0.43–1.75 mg/L), with average hs-CRP values of 0.71 mg/L in participants younger than 40 years of age and 1.2 mg/L in the older than 40 years. The difference in hs-CRP values between these two groups was statistically significant (p = 0.006). There was a significant positive correlation between hs-CRP and age (r = 0.266, p
Keywords: cardiovascular disease; high sensitivity c-reactive protein; military personnel; risk factor